2005
DOI: 10.1074/jbc.m504344200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Turnover Transfer of [2Fe2S] Clusters by the Iron-Sulfur Cluster Assembly Scaffold Proteins IscU and IscA

Abstract: IscU/Isu and IscA/Isa (and related NifU and SufA proteins) have been proposed to serve as molecular scaffolds for preassembly of [FeS] clusters to be used in the biogenesis of iron-sulfur proteins. In vitro studies demonstrating transfer of preformed scaffold- [FeS] The biosynthesis of iron-sulfur proteins is a multistep process involving a number of specialized proteins that mediate [FeS] cluster formation and delivery to acceptor proteins (reviewed in Refs. 1-3). One of the key features of the current vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 38 publications
6
105
0
Order By: Relevance
“…The inability to accomplish full activation of HydA DEFG may result from metal content heterogeneity and/or improper folding in purified HydA DEFG , either of which might result from heterologous expression in the absence of the full complement of maturation proteins. In addition, a decreased percentage of HydA DEFG activation is observed at higher HydF EG to HydA-D EFG ratios which is similar to effects observed for other systems in which scaffold proteins operate including the Isc and Nif systems [16,17].…”
Section: Investigating the Stoichiometry Of Hyda Defg Activation Bysupporting
confidence: 76%
“…The inability to accomplish full activation of HydA DEFG may result from metal content heterogeneity and/or improper folding in purified HydA DEFG , either of which might result from heterologous expression in the absence of the full complement of maturation proteins. In addition, a decreased percentage of HydA DEFG activation is observed at higher HydF EG to HydA-D EFG ratios which is similar to effects observed for other systems in which scaffold proteins operate including the Isc and Nif systems [16,17].…”
Section: Investigating the Stoichiometry Of Hyda Defg Activation Bysupporting
confidence: 76%
“…In addition, the observed reconstitution reaction is too slow to faithfully mimic the situation in vivo. This observation is similar to studies with bacterial Fe/S cluster assembly, which occurred at much slower rates than the in vivo process (18,19,53). We therefore conclude that an experimental system including only Nfs1p and Isu1p is too simple and additional components are required to better reflect the in vivo situation.…”
Section: Discussionmentioning
confidence: 42%
“…Recent elegant studies showed that E. coli IscU or Azotobacter vinelandii NifU are capable of catalyzing Fe/S cluster transfer to target proteins without the need of further assistance of a chaperone (14,18). Even multiple rounds of cluster transfer were documented.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine desulfurases provide sulfur from Lcysteine (11). Scaffolds are defined as being able to bind both iron and sulfur so that a Fe-S cluster can form before being transferred to targeted apoproteins (12)(13)(14)(15)(16)(17)(18). The SUF system includes an atypical cytosolic ABC-type transporter that functions with the cysteine desulfurase for increasing the production of sulfur (19,20).…”
mentioning
confidence: 99%